2m +3n=4
-m + 2n= 5
Multiply by 2 (-m + 2n = 5)
-2m + 4n = 10
2m + 3n = 4
Add the two equation
0 + 7n = 14
7n = 14
n = 2
To find m,
substitute n = 2 in 2m + 3n = 4
and solve for m
I'll let you finish
Check your answers when you find m
elimination using multiplication
2m +3n=4
-m + 2n= 5
Please Help!!!!
3 answers
2m+3n=4
2m+3*2=4
2m+6=4
2m=4-6
2m= -2 Divide with 2
m= -1
n=2 m= -1
2m +3n=4
Check of results:
2m+3n=4
2*( -1)+3*2=-2+6=4
-m+2n=5
-( -1)+2*2=1+4=5
2m+3*2=4
2m+6=4
2m=4-6
2m= -2 Divide with 2
m= -1
n=2 m= -1
2m +3n=4
Check of results:
2m+3n=4
2*( -1)+3*2=-2+6=4
-m+2n=5
-( -1)+2*2=1+4=5
i ahve no idea i need help!!!!!